THE NEED FOR 3D LASER SCANNING DOCUMENTATION FOR SELECT NIGERIA CULTURAL HERITAGE SITES - Odutola Christian Amans; Wu Beiping; Yao Yevenyo Ziggah; Abdul Ozovehen Daniel (European Scientific Journal, ESJ, 2013)
﻿Heritage sites documentation with 3D laser scanning has proven to be great way of preserving information and narratives about these sites in a very detailed and complete style to facilitate reconstruction if, peradventure, their significant part is lost to natural or man-made disaster. This spatial information forms not only an accurate record of rapidly deteriorating sites, which should be saved for posterity, but also provides a comprehensive base dataset by which heritage site managers, archaeologists and conservators can monitor and perform necessary restoration work to ensure physical integrity of cultural sites. In the past, traditional methods of documentation such as direct hand measurement and drawing at the point of capture have been used for documentation in West Africa heritage sites, for example Nigeria. These methods are not only time consuming but prone to several and large scale error especially when it requires high density point capture. This paper suggests way of documentation that will provide accurate data in shorter duration of time, especially for heritage structures with irregular and unmarked geometrical details, by using 3D laser scanning technology. This technology can produce detailed 3D model, two-dimensional (2D) drawing, and a guide to preservation and virtual reconstruction of heritage sites.